Biometric retina identification using artificial approach - Imam, Syed Abrar; Huda, Sheikh Samiul; Alam, Talha Bin; Ahsan, Anika (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.